Bioactive Benzofuran Neolignans from Aristolochia fordiana - Zhou, Zhong-bo; Luo, Jian-guang; Pan, Ke; Shan, Si-ming; Zhang, Wei; Kong, Ling-yi (Planta Medica, 2013)
Six new benzofuran neolignans (1–6) were isolated from the EtOAc-soluble fraction of the aerial part of Aristolochia fordiana, together with twelve known analogues (7–18). The structures of the isolated compounds were elucidated by spectroscopic methods. All isolates were evaluated for their inhibitory effects on nitric oxide production in lipopolysaccaride-activated RAW264.7 macrophages and for their cytotoxic activities on three human cancer cell lines. Compound 2 showed significant nitric oxide production inhibitory activity with an IC50 value of 10.00 µM, while compound 16 exhibited cytotoxic activity with an IC50 value of 11.9 µM against MG-63 and compound 18 of 9.15 µM against HepG2 cell lines, respectively.
Keywords: neolignans; Aristolochiaceae; Aristolochia fordiana; nitric oxide; cytotoxicity